Taxing profits in a changing world - Lucy Chennells; Rachel Griffith (Institute for Fiscal Studies (IFS), 1997)
This report looks at how corporate income taxes have changed over the past two decades, what incentives they provide for domestic and international investment, and whether changes in the international economy have helped shape these reforms.
Keywords: 330